ニホン ノルウェー コクサイ キョウドウ タイキキュウ カンソク ホウコク - 山岸, 久雄; ヤマギシ, ヒサオ; 小野, 高幸; オノ, タカユキ; 福西, 浩; フクニシ, ヒロシ; Yamagishi, Hisao; Ono, Takayuki; Fukunishi, Hiroshi (1983)
P(論文) 本報告は, 北欧における国際共同大気球観測3カ年計画の第2年次として, ノルウェー国において実施した大気球実験の経過と初期解析結果についてである。1982年3月19日および20日, ノルウェー国Stamsund (68°09′N, 13°46′E)において,オーロラ粒子降下と, それに関連した超高層物理現象を研究するため, 観測気球2基による実験を行った。実験は, 2基とも成功し, オーロラサブストーム時の電離層電場の変化, VLF電波の伝搬状態。X線microburst現象について, 良好な観測結果を得た。さらに3月4日より3月25日まで, ノルウェー国Andoya (69°18′N, 16°01′E)において, オーロラ活動に伴う, 超高層物理現象の地上観測をも実施した。 This report describes a result of the Japanese balloon campaign carried out in March 1982,at Stamsund (68°09′N, 13°46′E) in northern Norway. The objective of this campaign was to study auroral particle precipitation and related ionospheric phenomena. Two balloons were successfully launched on March 19 and 20,1982. The first one was launched in the recovery phase of an auroral substorm, and X-ray pulsation and microburst, correlated well with VLF emissions, were observed. The second one was launched at the substorm time, and the change of the ionospheric electric field direction was observed in association with auroral activities. The process of planning, the preparation and the operation for this campaign are also described for the convenience of future balloon campaign. departmental bulletin paper